2000
DOI: 10.1097/00004728-200005000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Papillary Serous Carcinoma of the Peritoneum: CT-Pathologic Correlation

Abstract: We present the CT findings of three cases of primary papillary serous carcinoma of the peritoneum. All patients presented with massive ascites. CT of the abdomen and pelvis showed omental caking in all patients. The parietal peritoneum of the pelvis showed diffuse enhancement with nodular thickening in all patients. No calcification was noted in the omental and parietal peritoneal masses, although psammoma bodies were present microscopically in one case. The ovaries were normal in size but showed a fine enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Calcifications within peritoneal and omental nodules represent psammoma bodies, and have been thought to be a distinguishing characteristic of EOPPC [18], however a recent review of three patients showed absence of calcification in all three patients. In that study, patients with EOPPC had massive omental caking and more extensive involvement of the pelvic peritoneum than the abdominal peritoneum, in the form of diffuse enhancing thickening with fine nodularity, creeping onto the ovarian and uterine surfaces [19]. This pattern of disease distribution was present in our patient on the MRI images and the CT portion of the PET/CT images and was confirmed on histopathological evaluation.…”
Section: Discussionsupporting
confidence: 74%
“…Calcifications within peritoneal and omental nodules represent psammoma bodies, and have been thought to be a distinguishing characteristic of EOPPC [18], however a recent review of three patients showed absence of calcification in all three patients. In that study, patients with EOPPC had massive omental caking and more extensive involvement of the pelvic peritoneum than the abdominal peritoneum, in the form of diffuse enhancing thickening with fine nodularity, creeping onto the ovarian and uterine surfaces [19]. This pattern of disease distribution was present in our patient on the MRI images and the CT portion of the PET/CT images and was confirmed on histopathological evaluation.…”
Section: Discussionsupporting
confidence: 74%
“…In a report by Zissin et al [14], six of 30 patients with serous surface papillary carcinoma had adnexal masses or ovarian enlargement on CT, but no evidence of tumor involvement was seen in the underlying ovaries or fallopian tubes on pathologic examination in any of the patients [14]. In the other three radiology studies, the ovaries were neither detected nor enlarged on CT [4,7,8].…”
Section: Discussionmentioning
confidence: 93%
“…Swerdlow [17] in 1959 first reported serous surface papillary carcinoma that was found in a patient with peritoneal carcinomatosis with no known primary lesion. Patients with serous surface papillary carcinoma are mostly found in a state of peritoneal carcinomatosis, which shows ascites, peritoneal thickening and nodules, and omental caking on CT and MRI [4,7,8,14]. Serous surface papillary carcinoma is found in 7-21% of patients with epithelial ovarian cancer [5,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations